SISTEM INFORMASI MANAJEMEN KINERJA DOSEN DAN TENAGA KEPENDIDIKAN BERBASIS KEY PERFORMANCE INDICATOR (KPI) STUDI KASUS UNIVERSITAS MUHAMMADIYAH PROF. DR. HAMKA - Arya Haydari Ramadhan; Armyko Rahmad Perbani; Muhammad Adi Samsul; Faisal Parshakh Nursyamsyi; Akhmad Rizal Dzikrillah (UHAMKA Press, 2022)
The process of monitoring and measuring the performance of an employee as well as archiving performance assessment data for lecturers and educational staff at UHAMKA so far has been carried out manually in paper form which causes a lack of efficiency in its implementation and the main obstacle faced during implementation is the lack of data integration. To overcome this problem, the creation of a Key Performance Indicator (KPI)-based performance management information system for lecturers and education staff can be a solution to facilitate the process of monitoring and measuring the performance of lecturers and students at UHAMKA. The creation of this system uses the Agile method with the Scrum framework because Scrum is a product development method that focuses on business value and has high flexibility for every need that is dynamic and sustainable. The results of this study are facilitating the process of integrating and archiving data as well as helping time efficiency in the KPI data management process for lecturers and students. The results of the satisfaction and success survey on the KPI system as a whole reached 88% so that this website can facilitate the KPI data management process at UHAMKA